Agronomy of grassland systems - Pearson, C. J. (Cambridge University Press, 1997)
The challenges facing grassland agronomists are becoming increasingly complex, with environmental and ethical issues assuming a greater significance alongside more conventional technical aspects. This new expanded edition, with an increased emphasis on systems thinking, has been revised to reflect current concerns, knowledge and practice. As such it addresses the need for a different approach to grassland agronomy, providing novel and provocative material to instruct, stimulate and enthuse the reader.